2013
DOI: 10.3390/molecules181012587
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Highly Fluorescent 8-Azapurine Ribosides Using a Purine Nucleoside Phosphorylase Reverse Reaction: Variable Ribosylation Sites

Abstract: Various forms of purine-nucleoside phosphorylase (PNP) were used as catalysts of enzymatic ribosylation of selected fluorescent 8-azapurines. It was found that the recombinant calf PNP catalyzes ribosylation of 2,6-diamino-8-azapurine in a phosphate-free medium, with ribose-1-phosphate as ribose donor, but the ribosylation site is predominantly N7 and N8, with the proportion of N8/N7 ribosylated products markedly dependent on the reaction conditions. Both products are fluorescent. Application of the E. coli PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…This ambiguity in the ribosylation sites in enzymatic reactions, catalyzed by PNP, was also previously observed in 8-azapurines [39,40], and probably results from the plasticity of the active site of this class of enzymes. For example, in the X-ray crystal structure of hexameric PNP from H. pylori, bound to an inhibitor formycin A (8-aza-N 9 -deazaadenosine), both the standard (anti) and non-standard (syn) conformations of the inhibitor were revealed [41].…”
Section: Enzymatic Syntheses Of the Tri-cyclic Ribosides And Their Prsupporting
confidence: 65%
“…This ambiguity in the ribosylation sites in enzymatic reactions, catalyzed by PNP, was also previously observed in 8-azapurines [39,40], and probably results from the plasticity of the active site of this class of enzymes. For example, in the X-ray crystal structure of hexameric PNP from H. pylori, bound to an inhibitor formycin A (8-aza-N 9 -deazaadenosine), both the standard (anti) and non-standard (syn) conformations of the inhibitor were revealed [41].…”
Section: Enzymatic Syntheses Of the Tri-cyclic Ribosides And Their Prsupporting
confidence: 65%
“…[72] Ribosides and deoxyribosides of 8-azaDaPur have been synthesized many years ago, [73,74] but their fluorescence properties were not examined until recently. We have found that enzymatically generated N9-, N8-, and N7-β-d-ribosides of 8-azaDaPur are highly fluorescent, [75] with yields of ca. 0.9, 0.4, and 0.06, respectively.…”
Section: 6-diamino-8-azapurine and The Corresponding Ribosidesmentioning
confidence: 99%
“…It is evident that some of the described compounds may be classified as "super photoacids." [34] It was found that many of the presented 8-azapurine analogs and their ribosides, including the nontypical N7-and N-8-β-d-ribosides, are accepted as substrates by enzymes of nucleoside metabolism, [75,76] and therefore can be applied as fluorescent probes of these systems.…”
Section: 6-diamino-8-azapurine and The Corresponding Ribosidesmentioning
confidence: 99%
“…It has been shown previously, that enzymatic ribosylation of some nucleobase analogs with PNP as a biocatalyst leads to non-typical ribosides, with ribose moiety attached not necessarily to purine N9, but also to other nitrogen atoms (Stachelska-Wierzchowska et al, 2013;Stachelska-Wierzchowska et al, 2016;Stachelska-Wierzchowska et al, 2018;Stachelska-Wierzchowska et al, 2019). In particular, while the E. coli PNP directs the ribosyl group predominantly to the N9 of ethenoadenine, the calf enzyme leads to almost exclusively N 6riboside (Stachelska-Wierzchowska et al, 2018).…”
Section: Resultsmentioning
confidence: 99%